RESPON SPESIFIK PUSKESMAS TERHADAP KEBUTUHAN SANITASI PENDUDUK PERMUKIMAN KUMUH DI BANTARAN SUNGAI CODE, KOTA YOGYAKARTA - Relmbuss Biljers Fanda; Mubasysyir Hasanbasri; Retna Siwi Padmawati (Jurnal Manajemen Pelayanan Kesehatan (The Indonesian Journal of Health Service Management), 2021)
Background: Gondomanan Primary Health Care (PHC) havethe toughest slums in the Code River, which Prawirodirjanvillage, but has made a declaration STBM in 2013.Objetive: To understand specifific response of PHC to sanitationneed of slum dweller in Code riverbank in Yogyakarta.Method: This research used a qualitative method. This studyused the case study, and data collection techniques in depthinterview. This research held in Prawirodirjan village. Theparticipants of this research were included 16 people, thatconsist of employees of Gondomanan PHC and Ministry ofHealth (MOH), infrastructure, enviroment agency, The HeadPrawirodirjan village, cadre of CLTS and slum communities.Results: CLTS that implemented in Gondomanan PHC hasreached the stage of the declaration. Gondomanan performsthe function of empowerment and coordination with otherstakeholders in CLTS with open defecation free (ODF).However, the achievement of the declaration still leavesproblems, namely the wrong faeces disposal, the diffiffifficulty ofaccess to communal wastewater treatment plant (WWTP), andthe source of water around the river polluted.Conclusion: Gondomanan PHC responded to the slumsdwellers needs of with implementing CLTS. Gondomanan PHCperformed the functions of public health leadership through themain functions of assessment, policy development andassurance. Although there were still weaknesses in theleadership of public health, but cooperation could be improved.